Anti-aspergillosis and anti-mucormycosis potential of essential oils from two Cymbopogon spp. targeting riboflavin synthesis pathway - Arun Dev Sharma; Inderjeet Kaur; Amrita Chauhan (Elsevier, 2023)
Background: Cymbopogon martinii (palmrose essential oil, PEO) and Cymbopogon citratus (lemon grass essential oil, (LEO) are used as complementary and traditional medicine worldwide. PEO and LEO from Cymbopogon genus, contains a diversity of pharmacologically active compounds. Due to the complex nature of essential oils, their antifungal mechanism of action against aspergillosis and mucormycosis is still not completely understood. Purpose: Hence, the present study aimed at determining the chemical profile of each PEO and LEO and performing a molecular docking of two of their components geraniol and geranial against fungal enzymes involved in riboflavin synthesis pathway viz: riboflavin synthase (RS), riboflavin biosynthesis protein RibD domain-containing protein (RibD), and 3,4-dihydroxy-2-butanone 4-phosphate synthase (DBPS) as opposite sites for drug designing against aspergillosis and mucormycosis and in vitro confirmation. Study design and method: Chemical profile of PEO and LEO was performed by GC-FID analysis. For molecular docking, patch-dock tool was conducted. Ligand-enzyme 3-D interactions were also calculated. ADMET properties (absorption, distribution, metabolism, excretion and toxicity) were also calculated. Antifungal activity was evaluated agaist three test pathogens Aspergillus niger, Aspergillus oryzae and Mucor indicus using poisoned food technique. Results: GC-FID showed geraniol/geranial as the major components in PEO/LEO, thus, they were selected for docking analysis. Docking analysis specified active binding of geraniol and geranial to riboflavin synthase (RS), riboflavin biosynthesis protein RibD domain-containing protein (RibD), and 3,4-dihydroxy-2-butanone 4-phosphate synthase (DBPS) fungal enzymes. Wet-lab authentication was achieved by three fungal strains A. niger, A. oryzae and M. indicus. Docking studies revealed that the ligands geraniol/geranial exhibited interactions with RS, RibD, and DBPS fungal enzymes by H- bond and hydrophobic interactions. Geraniol and geranial obeyed LIPINSKY rule, and exhibited adequate bioactivity. Wet lab results indicated that PEO/LEO was able to inhibit fungal growth against test pathogens. Conclusions: These findings confirm the fungicidal properties PEO/LEO essential oils as possible alternatives to synthetic fungicides.